Sohn-Rethel anthropologue ? - Frédéric Monferrand (Recherches Germaniques)
This article argues that the concept of “real abstraction” pertains to an ontology of commodity-producing societies, which, in order to be further developed, ought to be compared to the ontology of non-modern collectives as studied by anthropologists. The result of this comparison, which draws on Durkheim and Mauss’s account of “primitive forms of classification”, is that commodity-producing societies are defined by an ontological paradox: on the one hand, they are the only societies that regard themselves as conventional realities that are separated from nature and therefore transformable. But on the other hand, they are equally the only societies in which social relations impose themselves upon individuals as a blind ‘second nature’.